Plant abiotic stress physiology/ responses and adaption - Aftab, Tariq, (ed.); Hakim, Khalid Rehman,(ed.) (Boca Raton C R C press, 2022)
"Plant Abiotic Stress Physiology, 2-volume set highlights the various innovative and emerging techniques and molecular applications that are currently being used in plant abiotic stress physiology. Volume 1: Responses and Adaptations focuses on the responses and adaptations of plants to stress factors at the cellular and molecular levels and offers a variety of advanced management strategies and technologies. With contributions from specialists in the field, the volume discusses how plants have developed diverse physiological and molecular adjustments to safeguard themselves under challenging conditions and how emerging new technologies can utilize these plant adaptations to enhance plant resistance. Topics in this volume include redox homeostasis managers in plants, oxidative damage and antioxidative defense mechanism, photosynthesis and respiration under challenging environments, salinity-induced changes, genetics approaches for improving abiotic stress tolerance in crop plants, CRISPR/CAS-mediated genome editing technologies, and more. Agriculture today faces countless challenges to meet the rising need for sustainable food supplies and guarantees of high-quality nourishment for a quickly growing population. To assure sufficient food production, it is necessary to address the difficult environmental circumstances that are causing cellular oxidative stress in plants due to abiotic factors, which play a defining role in shaping yield of crop plants. This volume, in conjunction with Plant Abiotic Stress Physiology: Volume 2: Molecular Advancements, helps to meet these challenges by providing a rich source of information on plant abiotic stress physiology and effective management techniques"--
Keywords: Plants--Effect of stress on